Directors’ Duties and Corporate Social Responsibility under German Law – Is Tort Law Litigation Changing the Picture? - Peter Rott (Nordic Journal of Commercial Law, 2017)
This article discusses the right and a potential duty of directors to pursue CSR policies under German law. It first explains the two main duties of directors: to make sure that the company complies with its legal obligations, which has been broadly interpreted in Germany to include the duty to extend to domestic and foreign subsidiaries’ compliance with the law, and to act for the (economic) benefit of the company. CSR policies will often only come under the second duty, which means that they can be pursued if they are economically beneficial. However, acting in order to benefit the company also means the avoidance of unnecessary risk, including the risk of tort law liability. This article discusses how recent tort law development towards a duty of care of parent companies for employees of their subsidiaries, and perhaps even victims of their subsidiaries’ operations, as triggered by the English landmark case of Chandler v Cape, has created risks for parent companies that affect the duty of their directors to establish a corporation-wide system of prevention. It is argued that those liability risks are substantive in amount but uncertain due to the early state of case law, with a number of relevant cases pending at this moment; which allows directors a certain margin of appreciation. The article concludes that the tort law development has certainly strengthened the right of directors to pursue a CSR policy that avoids liability, while a corresponding duty of directors may arise and intensify with the influx of more transnational tort law cases and, in particular, with judgments in favour of victims of torts committed in the course of operations of transnational corporations in developing countries.